ISSUES OF THE GENESIS OF THE MIDDLE AGES MEDESES OF THE MIDDLE ASIAN REGION - Ochilova, S.; Ochilova, S. (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses the origins of the construction of madrasas in medieval Central Asia, their purpose, protection from the side of enlightened representatives of the peoples of the region.